Homo communicans - Smoleń, Jerzy (Vox Patrum, 2008)
Herbert Marshall McLuhan acknowledged the invention of the print as a beginning of a new age in the field of human communication. Indeed, communication is indissolubly linked with the progress of humanity in this twenty-first century when human being is called „homo communicans”. The process of communication is complicated. Experts from many different disciplines are still reflecting and trying to make human communication more proper and effective. The systems of communication are very important features in the functioning of the contemporary world and they are permanently updated. Owing to information a human being deepens his knowledge, which should serve him always to accomplish his development goals and never can leads him to degradation.